2010
DOI: 10.1253/circj.cj-09-0409
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Vivo Expanded Umbilical Cord Blood Stem Cells Retain Capacity for Myocardial Regeneration

Abstract: Background: Umbilical cord blood (UCB) is a source of human hematopoietic precursor cells (HPCs), a stem cell (SC) type that has been used in several trials for myocardial repair. A certain minimal number of cells is required for measurable regeneration and a major challenge of SC-based regenerative therapy constitutes exvivo expansion of the primitive cell compartment. The aim of this study was to investigate the ex-vivo expansion potential of UCB-derived HPCs and the ability of these expanded cells to migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…These reports suggest that poor responses to cellular therapy are due to quantitative and/or qualitative impairment of the EPC fraction. To further augment the efficacy of EPC transplantation, several methodological approaches to enhance EPC bioactivities are currently being developed [5,[23][24][25][26][27][28].…”
Section: Several Translational Researchers Have Demonstrated That Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…These reports suggest that poor responses to cellular therapy are due to quantitative and/or qualitative impairment of the EPC fraction. To further augment the efficacy of EPC transplantation, several methodological approaches to enhance EPC bioactivities are currently being developed [5,[23][24][25][26][27][28].…”
Section: Several Translational Researchers Have Demonstrated That Cd34mentioning
confidence: 99%
“…In this regard, the several culture systems of suspended EPC phenotype have been developed and demonstrated the significance of EPC expansions ex vivo and the efficiency of cultured CD34 ϩ or CD133 ϩ cell transplant for neovascularization in ischemic animal models [5,[23][24][25][26][27][28].…”
Section: Protocols and Manufacturing For Cell-based Therapiesmentioning
confidence: 99%
“…Therefore, the field of tissue engineering has great potential in identifying new transplant strategies to provide better quality of life (Angiolillo & Goto, 2010;Limbourg, Limbourg, & Drexler, 2009;Shlechta et al, 2010). The creation of scaffolds that can be used for the development of complex three-dimensional tissues or whole organs remains a serious challenge in tissue engineering (Gálvez-Mónton, Prat-Vidal, Roura, Soler-Botija, & BayesGenis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Thus far, it has been shown that various populations of stem cells, such as bone marrow mesenchymal stem cells, 5 white adipose-derived stem cells, 6 umbilical cord blood stem cells, 7 and resident cardiac stem cells, 8 are capable of producing CMs to inhibit further deterioration and help restore cardiac function caused by ischemic heart disease. However, the differentiation ability of these stem cells into CMs was assisted by the stimulation of chemical inducers.…”
Section: Introductionmentioning
confidence: 99%